Consumer attitude and preference in the Islamic mortgage sector: a study of Malaysian consumers - Amin H.; Abdul Rahman A.R.; Abdul Razak D.; Rizal H. (Emerald Group Publishing Ltd., 2024)
Indexed by WOS/SCOPUS/ERA